A bacteriological study of acute exacerbation of chronic obstructive pulmonary disease over a period of one year - Narayanagowda, Devanath Sosale; Golia, Saroj; Jaiswal, Jyoti; Manasa, Suhani Srinivas (International Journal of Research in Medical Sciences, 2017)
Background: The aim of our study was to analyse the hospital data on AECOPD in patients with special reference in males and female cases, the pathogens involved, antibiotic susceptibility pattern. Methods: 107 patients (72 males, 35 females) aged between 45 and 85 years were included in the study. A detail history was elicited and complete examination was done. The sputum specimen was collected using sterile sputum cups and subjected to Gram’s stain, culture and biochemical reactions. Results: Our study shows 44 positive sputum cultures out of total 107 cases. Out of 107 cases 67% were males and 33% were females. The predominant clinical feature observed in our study was cough with expectoration, exertional dyspnoea and production of mucopurulent sputum. The prevalence of Gram negative bacteria was 55% and Gram positive bacteria was 45%. Klebsiella pneumoniae was the commonest bacteria isolated (38%) followed by Staphylococcus aureus (18%). The drug sensitivity reveals that 79.55% of the isolates were sensitive to amikacin followed by 68.18% sensitive to amoxyclavulinic acid and 54.55% of the isolates were sensitive to ciprofloxacin. Conclusions: In a developing country like India AECOPD is more common in adults more than 55 years of age due to smoking habits and high indoor pollution. This leads to a major impact on the quality of life of patients with the condition. They are a major cause of hospital admission and health care utilization.